Decoupling the effects of food and density on life‐history plasticity of wild animals using field experiments: Insights from the steward who sits in the shadow of its tail, the North American red squirrel. Issue 11 (19th October 2020) - Dantzer, Ben; McAdam, Andrew G.; Humphries, Murray M.; Lane, Jeffrey E.; Boutin, Stan
Abstract: Long‐term studies of wild animals provide the opportunity to investigate how phenotypic plasticity is used to cope with environmental fluctuations and how the relationships between phenotypes and fitness can be dependent upon the ecological context. Many previous studies have only investigated life‐history plasticity in response to changes in temperature, yet wild animals often experience multiple environmental fluctuations simultaneously. This requires field experiments to decouple which ecological factor induces plasticity in fitness‐relevant traits to better understand their population‐level responses to those environmental fluctuations. For the past 32 years, we have conducted a long‐term integrative study of individually marked North American red squirrels Tamiasciurus hudsonicus Erxleben in the Yukon, Canada. We have used multi‐year field experiments to examine the physiological and life‐history responses of individual red squirrels to fluctuations in food abundance and conspecific density. Our long‐term observational study and field experiments show that squirrels can anticipate increases in food availability and density, thereby decoupling the usual pattern where animals respond to, rather than anticipate, an ecological change. As in many other study systems, ecological factors that can induce plasticity (such as food and density) covary. However, our field experiments that manipulate food availability and social cues of density (frequency of territorial vocalizations) indicate that increases in social (acoustic) cues of density in the absence of additional food can induce similar life‐history plasticity, as does experimental food supplementation. Changes in the levels of metabolic hormones (glucocorticoids) in response to variation in food and density are one mechanism that seems to induce this adaptive life‐history plasticity. Although we have not yet investigated the energetic response of squirrels to elevated density or its association with life‐history plasticity, energetics research in red squirrels has overturned several standard pillars of knowledge in physiological ecology. We show how a tractable model species combined with integrative studies can reveal how animals cope with resource fluctuations through life‐history plasticity. Abstract : Infographic summarizing key insights about life‐history responses of North American red squirrels in the Yukon, Canada to variation in food availability and population density as well as experimental manipulations of food and density.